2020
DOI: 10.3389/fpubh.2020.00402
|View full text |Cite
|
Sign up to set email alerts
|

Treating Psychological Trauma in the Midst of COVID-19: The Role of Smartphone Apps

Abstract: With the COVID-19 pandemic confronting health systems worldwide, medical practitioners are treating a myriad of physical symptoms that have, sadly, killed many thousands of people. There are signs that the public is also experiencing psychological trauma as they attempt to navigate their way through the COVID-19 restrictions impinging on many aspects of society. With unprecedented demand for health professionals' time, people who are unable to access face-to-face assistance are turning to smartphone apps to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Moreover, to protect newborns, a mother should limit the number of people they have contact with (44). Finally, other online strategies, such as online mental health services or telemedicine, can help alleviate the psychological problems of pregnant women by communicating with others remotely (51)(52)(53).…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Moreover, to protect newborns, a mother should limit the number of people they have contact with (44). Finally, other online strategies, such as online mental health services or telemedicine, can help alleviate the psychological problems of pregnant women by communicating with others remotely (51)(52)(53).…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Five reviews that were identified in the literature examined apps that could be used in symptoms management of PTSD. 16,[49][50][51][52] One of these reviews looked at the content and published data on 5 apps' effectiveness, 50 and 2 reviews examined 30 apps and 69 apps using content analysis, respectively,. 49,51 and 16 apps included in these reviews were endorsed by the US Departments of Veteran Affairs' NCPTSD.…”
Section: Ptsdmentioning
confidence: 99%
“…89 Furthermore, if apps purport to be evidence based and have underpinnings that follow proven principles of behavioural change, health care providers who do not have a specialized background in the subject matter (e.g., in trauma management) might recommend apps that may not have sufficient evidence to assess their effectiveness. 52 ICER recommended that all manufacturers of digital health technologies should provide "robust evidence of the clinical effectiveness and broader impact… a minimum evidence requirement is high-quality observational or quasi-experimental studies with an appropriate comparator and relevant patient outcomes" (P. 3) 73 A review of studies that assessed safety of health apps found over 80 safety concerns within health apps -including health misinformation (e.g., bipolar disorder is contagious), incomplete information (e.g., missing key information areas for cardiovascular disease), variation in content (e.g., different information required for the same disease in different apps), incorrect outputs (e.g., incorrect diagnoses), and inappropriate responses (e.g., not responding appropriately to suicidal ideation). 90 A concern for public health in the rapid creation of health apps is the potential for growth that does not meet demand for these apps.…”
Section: Operational Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While evidence exists for the benefits of digital interventions on clinical populations living with severe mental disorders, digital psychiatry evaluation research in low-income and middle-income countries remains to be scarce and open for exploration (Merchant et al, 2020). Reports of people increasingly turning to smartphone mental health apps to help them deal with pandemic-imposed psychological trauma are a bit problematic (Marshall et al, 2020) because of the inherent limitations involved in the use of such apps without the guidance of a professional. These are just some of the things that clinicians need to be aware of.…”
mentioning
confidence: 99%